Weight reduction after bariatric surgery improves myocardial work indices and global longitudinal strain. (4th February 2022) - Sinski, M; Piechocki, K; Styczynski, G; Szmigielski, CA; Bidiuk, J; Lewandowski, J
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Obesity is known to affect cardiovascular morphology, function and outcomes. Most parameters used to evaluate cardiac function, especially ejection fraction, but also strain are load dependent and the research focused on the effects of the weight loss on cardiac systolic function are inconsistent.  Myocardial work is a novel cardiovascular parameter that characterizes cardiac systolic function and is less load dependent. However, there is lack of data how bariatric surgery affects parameters of the non-invasively calculated myocardial work indices obtained from pressure-strain loops obtained in patients referred with severe obesity. Purpose: The purpose of the study was to analyze whether myocardial work indices change after bariatric surgery. Methods: Out of 171 consecutive subjects that were referred to bariatric surgery and characterized elsewhere (1) 15 subjects, that had both, adequate visualization, and post- surgery transthoracic echo (TTE) performed, were taken into analysis. Echocardiographic examination was performed using GE Vivid 9 and analyzed with EchoPac 204 software. Results: Global myocardial work (GWI), global constructive work (GCW) and global work efficiency (GWE) indexes increased, while global wasted work index (GWW) decreased significantly after bariatric surgery (Figure). GLS increased significantly after bariatric surgery (Figure). LV ejection fraction did not change significantly after surgery (60.2 ± 6.5% vs. 60.9 ± 7 %, p = 0.68). LV end-diastolic diameter (LVEDD) did not change (4.86 cm ± 0.35 vs. 4.89 cm ± 0.38, p = 0.55), while posterior wall thickness (PW) and relative wall thickness (RWT) decreased significantly (1.08 ± 0.13 vs. 0.99 ± 0.13, p = 0.001 and 0.45 ± 0.05 vs. 0.41 ± 0.06, p= 0.0003, respectively). Left atrial diameter (Figure) and left atrial area were lower after bariatric surgery (18.6 cm2 ± 2.5 vs. 16.7 cm2 ± 2.5, p = 0.027). Both systolic blood pressure and heart rate decreased after bariatric surgery (Figure). Mean time to post – surgery TTE was 400 days ± 151 and mean weight reduction was 38 kg ± 8. Conclusion: Left ventricular systolic function evaluated using myocardial work indexes increased after bariatric surgery. After bariatric surgery, the myocardial work parameters returned to normal range, when based on the values recorded in the reference STAAB cohort study (2).